An inclusive profile for support teachers in training: The effectiveness of the specialization program at the University of Turin - Bellacicco, Rosa (Education Sciences & Society - Open Access, 2019)
Developing competences for inclusive education in future support teachers is essential to ensure that they become not only experts in interventions on students with disabilities but are prepared to face the broad challenges of the school of differences. This study examined the effectiveness of the specialization program in Special Education organised by the University of Turin (2016/17) in enhancing teachers’competences and knowledge on inclusion. The teaching strategies used during the program, which were more associated with this purpose, and the application of acquired skills in classroom were also examined. 180 teachers participated in the survey, completing a questionnaire based on the Profile of inclusive teachers (EADSNE, 2012). The results indicate that the program had positive effects, moderate-to-large, in increasing teachers’ competences and knowledge on inclusion. In addition, most of the trainees was also able to implement these in schools. Regarding the teaching practices, the opportunity of dialogue with other trainees, and the teaching experience in school placements were perceived by participants as the most incisive.